2016
DOI: 10.18632/oncotarget.10430
|View full text |Cite
|
Sign up to set email alerts
|

P2×7 targeting inhibits growth of human mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumor refractory to anti-blastic therapy. MPM cells show several genetic and biochemical defects, e.g. overexpression of oncogenes, downregulation of onco-suppressor genes, dysregulation of microRNA, or alteration of intracellular Ca2+ homeostasis and of apoptosis. No information is as yet available on purinergic signalling in this tumor. Signalling via the P2×7 (P2RX7 or P2×7R) purinergic receptor is attracting increasing attention as a pathway involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 36 publications
(53 reference statements)
3
46
1
Order By: Relevance
“…Adinolfi and colleagues first demonstrated the growth-promoting activity of P2X7 in four different tumor models in mice including HEK-293 cells and ACN neuroblastoma derived xenografts and syngeneic colon carcinoma and melanoma models (Adinolfi et al, 2012a). Several studies have confirmed these data and extended them, demonstrating that P2X7 blockade leads to a general reduction of tumor burden in neuroblastoma (Amoroso et al, 2015;Ulrich et al, 2018), mesothelioma (Amoroso et al, 2016), melanoma Adinolfi et al, 2015a), glioma (Ji et al, 2018), osteosarcoma (Zhang et al, 2019a) and myeloid leukemia (De Marchi et al, 2019a).…”
Section: Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adinolfi and colleagues first demonstrated the growth-promoting activity of P2X7 in four different tumor models in mice including HEK-293 cells and ACN neuroblastoma derived xenografts and syngeneic colon carcinoma and melanoma models (Adinolfi et al, 2012a). Several studies have confirmed these data and extended them, demonstrating that P2X7 blockade leads to a general reduction of tumor burden in neuroblastoma (Amoroso et al, 2015;Ulrich et al, 2018), mesothelioma (Amoroso et al, 2016), melanoma Adinolfi et al, 2015a), glioma (Ji et al, 2018), osteosarcoma (Zhang et al, 2019a) and myeloid leukemia (De Marchi et al, 2019a).…”
Section: Proliferationmentioning
confidence: 99%
“…In these settings, P2X7 mediated calcium signaling was shown to trigger intracellular signaling and changes in gene expression that are critical for cancer cell survival and proliferation (Di Virgilio, 2015;Di Virgilio et al, 2018a). Indeed, overexpression of full length P2X7 was shown to promote tumor growth (Jelassi et al, 2011;Adinolfi et al, 2012a), while P2X7 blockade was shown to inhibit neoplastic growth in several experimental models (Adinolfi et al, 2012a;Adinolfi et al, 2015a;Amoroso et al, 2015;Amoroso et al, 2016;Giannuzzo et al, 2016;De Marchi et al, 2019;Zhang et al, 2019a). .…”
Section: P2x7 Possesses Ion Channel Functionalitymentioning
confidence: 99%
“…Many studies using P2X7 inhibitors and antagonist have rendered promising results, reducing cancer growth or spreading in preclinical animal models of colon cancer (Adinolfi et al, 2012 ), breast cancer (Jelassi et al, 2011 ; Park et al, 2016 ), ovarian cancer (Vázquez-Cuevas et al, 2014 ), pancreatic ductal adenocarcinoma (Giannuzzo et al, 2016 ), neuroblastoma (Amoroso et al, 2015 ), melanoma (Adinolfi et al, 2012 , 2015 ), glioma (Ryu et al, 2011 ), and mesothelioma (Amoroso et al, 2016 ). The pharmacological molecules used to block P2X7 in those studies were administrated either intratumorally or systemically and included oATP (Adinolfi et al, 2012 ; Hattori and Gouaux, 2012 ), BBG (Vázquez-Cuevas et al, 2014 ), AZ10606120 (Adinolfi et al, 2012 , 2015 ; Amoroso et al, 2015 , 2016 ; Giannuzzo et al, 2016 ), A740003 (Adinolfi et al, 2015 ; Amoroso et al, 2015 ), A438079 (Jelassi et al, 2011 ), Antraquinone emodin (Jelassi et al, 2013 ), novel 1-Piperidinylimidazole based antagonists (Park et al, 2016 ), and P2X7 blocking antibodies (Ren et al, 2010 ). Many pharmaceutical companies are attempting to develop a clinical candidate targeting P2X7 receptor and various scaffolds have been disclosed (Park and Kim, 2017 ).…”
Section: P2x7 Receptor In Cancer—angel or Demon Depending On Its Levementioning
confidence: 99%
“…These studies have shown that MPM is characterized by increased cell proliferation (downregulation of tumor suppressor genes, overexpression of oncogenes), inhibition of apoptosis ( 39 , 40 ), and alteration of intracellular Ca 2+ homeostasis ( 41 , 42 ). There is evidence that some of these molecular alterations, such as overexpression of adenosine A3 receptor ( 43 ), purinergic receptor P2X7 ( 40 ) and dysregulation of cellular ( 44 ) and circulating microRNAs (miRNAs) ( 27 , 45 ) could be used to diagnose and interfere with MPM growth. The literature related to the most commonly found alteration in MPM is discussed below, with special emphasis on those pathways that could be exploited in the future for early diagnosis and the treatment of MPM.…”
Section: Molecular Mechanisms Underlying Mpmmentioning
confidence: 99%